PENGARUH RADIASI SMARTPHONE DALAM KONDISI AIRPLANE MODE TERHADAP HISTOLOGI GINJAL MENCIT BETINA - Mellani Rachma; Fhuji Winardi; Yusni Atifah; Dwi Hilda Putri; Maulia Indah Ayuningtyas; Echa Azkia Afandi (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
The rapid advancement of technology and information has led to a significant increase in smartphone usage in Indonesia, reaching 67.88% in 2022. Smartphones emit non-ionizing electromagnetic waves that may pose biological effects, particularly on the kidneys, which play a crucial role in maintaining the body's homeostasis. Previous studies have reported that electromagnetic radiation can induce histological damage in the kidneys through oxidative stress mechanisms, including tubular narrowing, Bowman’s capsule dilation, and tubular epithelial necrosis. Airplane mode is known to significantly reduce electromagnetic radiation exposure. This study aimed to determine the effect of smartphone radiation in airplane mode on the kidney histology of female mice. An experimental design was employed using four female mice divided into one control group and three treatment groups, which were exposed to a smartphone in airplane mode for 4, 6, and 8 hours per day for 7 consecutive days. Kidney tissues were processed using paraffin embedding and stained with Hematoxylin–Eosin for microscopic examination. The results showed no significant histological differences between the control and treatment groups. The glomerulus, Bowman’s capsule space, and proximal and distal convoluted tubules appeared normal without signs of narrowing, dilation, hemorrhage, or necrosis. These findings indicate that smartphone radiation in airplane mode does not cause histological damage to the kidneys of female mice.